O papel do educador social voluntário no processo de inclusão de estudantes com transtorno do espectro autista - Silva, Gisele Eduardo de Oliveira (2018)
In the last decades, several international movements have appeared in favor of a more inclusive and less segregator system of education. In Brazil, inclusion was influenced by ideals of education from Europe and the United States. In relation to rights for students with Autism Spectrum Disorder (ASD), the Berenice Piana Law presents a significant support figure in the process of inclusion of this audience, the specialized companion, as long as their need is proven. In the Federal District (FD), this support is provided by a teaching assistant which is a Volunteer Social Educator (VSE). Considering the VSE as a support for the educational inclusion of the student with ASD leads to the need to reflect on pedagogical policies and practices directed at them, due to the challenges education faces. Moreover, it is debatable whether the rights of these students are being guaranteed, since not even the federal legislation guarantees the profile of this aid figure. This being true, the scarcity of research related to the VSE in the realm of educational inclusion is detected. From a broader perspective, this research investigates the inclusive process of students with ASD in reverse integration classes of mainstream school, to discover relevant aspects about the role of volunteer social educator, order to promote the educational inclusion of this public. The research aimed to investigate whether the volunteer social educator's role in the classroom in the process of including the student with ASD contributes to the success of their school performance or corroborates a veiled exclusion. The methodology used was exploratory qualitative research. It is a multiple cases study with one unit of analysis. The sources of evidence used were document analysis, observations and interviews. The research participants were two teachers, two VSE, a director and an educational counselor from two mainstream schools of the FD public school system in which they studied children with ASD in reverse integration classes accompanied by VSE. Exclusion processes were identified in both cases, although the importance of this educational support is acknowledged. The research revealed the necessity of continuous work in relation to the formation of the VSE. The way in which district legislation is supplying the specialized companion, to which the TEA student is entitled, has not been sufficient to guarantee the right to learn from the whole individual formation perspective.